If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 + -4 = 4x + 3 + -6x Reorder the terms: 7 + -4 + 2x = 4x + 3 + -6x Combine like terms: 7 + -4 = 3 3 + 2x = 4x + 3 + -6x Reorder the terms: 3 + 2x = 3 + 4x + -6x Combine like terms: 4x + -6x = -2x 3 + 2x = 3 + -2x Add '-3' to each side of the equation. 3 + -3 + 2x = 3 + -3 + -2x Combine like terms: 3 + -3 = 0 0 + 2x = 3 + -3 + -2x 2x = 3 + -3 + -2x Combine like terms: 3 + -3 = 0 2x = 0 + -2x 2x = -2x Solving 2x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2x + 2x = -2x + 2x Combine like terms: 2x + 2x = 4x 4x = -2x + 2x Combine like terms: -2x + 2x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 5x^2-10xy= | | 5x^2+6x= | | 6x^4+13x^3-5x^2-3x+1=0 | | 1/4y=-5 | | 14x-10x= | | x^2-16x+5x=0 | | =2x-3y+x+2y | | 100+50t=100 | | 6x-7=6(x+9) | | x^2=3y+15 | | 12-8x=177-43x | | 4x^4=36 | | x-1/5-2=x-3/4 | | 1/4=x+5/4 | | 2x-17=4x+3 | | y/(y-6)=(-2)/(y-1) | | 9x+17=4x+3 | | 3G+3d= | | -b-7=-1 | | 9(y+2)=3(2y+3) | | 11x-(6x-4)=44 | | 6y+15x=12 | | 11x(6x-4)=44 | | x^2+xy=30 | | x^2-15x-12=0 | | 2n=4+20 | | -(x-1)x-9(x-1)=0 | | -2n+11=5 | | 3n-7=20 | | 8(w-3)=4(3-w) | | X^3-24x=0 | | -2/3t+2-3/4t=-4 |